PENGARUH INTENSITAS KOMUNIKASI DALAM KELUARGA DAN TINGKAT KEDEKATAN FISIK TERHADAP INTIMATE RELATIONSHIP - Desy Nurulita; Agus Naryoso; Sri Budi Lestari; Nurriyatul Lailiyah (Interaksi Online, 2016)
Background of this research is caused by the condition in this modern era, when both parents working that makes low intensity of communication in family. Modern society work very hard and have a very little time to gather with family. This is why so many parents don’t have a good phisical proximity even emotional proximity to their children. Whereas communication during adolescence ia a significant challenge for parents. The result shows that intensity of family communication has the effect to intimate relationship which influenced by some factors like frequency and duration of meet, call and send message to their family. Phisical proximity has the effect to intimate relationship which influenced by some factors like frequency of  gather, eat, hang out, doing hobby, holiday, sleep, and pray together with family. And intensity of family communication and phisical proximity has the effect to intimate relationship as many as 33,2%.